2020
DOI: 10.1080/23812346.2020.1745411
|View full text |Cite|
|
Sign up to set email alerts
|

Opinions from the epicenter: an online survey of university students in Wuhan amidst the COVID-19 outbreak1

Abstract: The outbreak of the novel coronavirus (2019-nCov, COVID) in Wuhan, China, in December 2019 quickly escalated into a global health emergency. This study seeks to investigate the attitudinal and behavioral patterns of university students in Wuhan, the epicenter. Conducted in late January 2020, an online survey collected data from more than 8000 students of four elite national universities located in Wuhan. The students sampled included both Wuhan natives and non-locals who returned home in the early stages of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 23 publications
1
104
1
8
Order By: Relevance
“…Several sources of stressors related to pandemics and their Public Health management have been described in the past, such as the unpredictable nature of the disease [ 7 , 8 ], the lack of timely and transparent information disclosure by authorities [ 3 ], the loss of personal freedom, sudden changes and impossibility of future planning and social distancing, together with the worry about one’s own health and that of one’s relatives and acquaintances [ 8 ], and the large financial losses expected [ 9 ]. A recent systematic review on the psychological impact of previous confinements related to the Ebola, H1N1 influenza, Middle East respiratory syndrome (MERS-CoV) and equine influenza disease outbreaks, found that a long duration of quarantine, fear of infection, inadequate information, stigma, or financial loss were related to higher levels of anxiety, anger, confusion, and post-traumatic stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several sources of stressors related to pandemics and their Public Health management have been described in the past, such as the unpredictable nature of the disease [ 7 , 8 ], the lack of timely and transparent information disclosure by authorities [ 3 ], the loss of personal freedom, sudden changes and impossibility of future planning and social distancing, together with the worry about one’s own health and that of one’s relatives and acquaintances [ 8 ], and the large financial losses expected [ 9 ]. A recent systematic review on the psychological impact of previous confinements related to the Ebola, H1N1 influenza, Middle East respiratory syndrome (MERS-CoV) and equine influenza disease outbreaks, found that a long duration of quarantine, fear of infection, inadequate information, stigma, or financial loss were related to higher levels of anxiety, anger, confusion, and post-traumatic stress [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study conducted with Chinese university students, it was determined that 42.7% of the partici- pants ate garlic to be protected from COVID-19. 16 This researcher is unable to find any scientific study demonstrating that a single food is effective in protecting from COVID-19. It is known that most university student diets are not nutritionally adequate or balanced during their school years.…”
Section: Discussionmentioning
confidence: 99%
“…Some residential blocks were sealed off while all residents had to enter or leave via a single gate guarded by grid controllers on a 24-7 basis. 11 Many research reports as well as anecdotal materials suggest an extremely heavy-handed enforcement of community lockdown and social distancing not only in Wuhan but also in many other parts of China (Yang, Bin, and He 2020;He et al 2020).…”
Section: Mobilizing Resourcesmentioning
confidence: 99%